PENEGAKKAN HUKUM DALAM PERSPEKTIF AL-QURAN STUDI TAFSIR IBNU KATSIR - Adrianto; Haslinda; Chalid Sitorus (JIQSI : Jurnal Ilmu Al Qur'an dan Studi Islam, 2025)
Abstract This study aims to describe Increasing how law enforcement In the perspective of the Quran study tafsir of ibnu katsir the data collection technique is using library research or library study research with data collection techniques carried out by examining literature, document, and other sources of information related to the Topik of researchers. The result of this study the first, Ibnu Katsir a prominent Islamic scholar and commentator, strongly opposes manipulation of the law for the benefit of a particular person or group According to him, the law of Allah (Syariah) must be applied fairly and objectively without any attempt to benefit or harm a particular party The second, according to Ibn Kathir, people of islam called upon to uphold justice in every action they take reflects faith and their devotion to God Justice must be a basic principle in all aspects of life In all aspects - social, economic, and political - justice is a sacred obligation and an integral part of faith.